Valivalamummaṇikkōvai : kuṟippuraiyuṭaṉ - Cāminātaiyar, U. Vē., 1885-1942 (SAMP early 20th-century Indian books project, 1934)
Verse work in praise of Siva (Hindu deity) enshrined at Valivalam, Thañjāvūr District, Tamil Nadu; with interpretive notes.